Study of the central auditive pathway by encephalic trunk evoked e auditory responses (ear) in children with language retard - Gallardo, Manuel (2003)
Objetive: To determine the functional integrity of the brainstem auditory pathway by the auditive brainstem response (ABR) in language-retarded children without pathology in both the middle ear and central nervous system and no neonatal hearing loss risk factors. Design: Retrospective transversal study. Setting: Naval Medical Center and Air Force Central Hospital Otorhinolaryngology Services, Lima. Peru. Material and methods: Analysis of children’s ABR performed in the last ten years included 48 children, 28 males and 20 females, 1 to 11 year-old. Main outcome measures were both latency time and morphology of waves I, II, III, IV, and V. Results: Latencies were normal at any age. Morphological distortion and/ or wave hypovoltage were found in 77% of the patients, more frequently (58%) in waves I and II that correspond to the auditory nerve and brainstem cochlear nuclei. Conclusions: The results suggest a disturbance in the neural synchronization of the auditory pathway and the brainstem nuclei in 77% of the patients studied, that would affect the central auditory processing.